2017
DOI: 10.1109/tuffc.2017.2748050
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Hydrophone Aberration Correction for Transcranial Histotripsy Treatment of Intracerebral Hemorrhage: Proof-of-Concept

Abstract: Histotripsy is a minimally invasive ultrasound therapy that has shown rapid liquefaction of blood clots through human skullcaps in an in-vitro intracerebral hemorrhage (ICH) model. However, the efficiency of these treatments can be compromised if the skull induced aberrations are uncorrected. We have developed a catheter hydrophone which can perform aberration correction and drain the liquefied clot following histotripsy treatment. Histotripsy pulses were delivered through an excised human skullcap using a 256… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Cationic lipid-shelled MBs (Fig. 3a) were synthesized according to recently published methods (Gorick et al 2020). Briefly, a micellar aqueous mixture of 2 mg/mL 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC, Avanti Polar Lipids, Alabastar, AL, USA), 2 mg/mL polyethylene glycol 6000 monostearate (PEG 6000 MS; Stepan Kessco, Northfield, IL, USA), and 0.8 mg/mL 1,2-distearoyl-3-trimethylammonium-propane (DSTAP, Avanti Polar Lipids) in 0.9% NaCl (Baxter, Deerfield, IL, USA) was prepared by probetype sonication (20 kHz, 3 min, 50% power, XL2020 instrument, Misonix Inc., Farmingdale, NY, USA).…”
Section: Formulation Of Gas-filled Mbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cationic lipid-shelled MBs (Fig. 3a) were synthesized according to recently published methods (Gorick et al 2020). Briefly, a micellar aqueous mixture of 2 mg/mL 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC, Avanti Polar Lipids, Alabastar, AL, USA), 2 mg/mL polyethylene glycol 6000 monostearate (PEG 6000 MS; Stepan Kessco, Northfield, IL, USA), and 0.8 mg/mL 1,2-distearoyl-3-trimethylammonium-propane (DSTAP, Avanti Polar Lipids) in 0.9% NaCl (Baxter, Deerfield, IL, USA) was prepared by probetype sonication (20 kHz, 3 min, 50% power, XL2020 instrument, Misonix Inc., Farmingdale, NY, USA).…”
Section: Formulation Of Gas-filled Mbsmentioning
confidence: 99%
“…Cavitation bubble clouds induce high stress and strain in the target tissue at the subcellular level, resulting in complete tissue disintegration into an acellular homogenate with no remaining cellular structures (Vlaisavljevich et al 2013b(Vlaisavljevich et al , 2016c. Because of these features, histotripsy is being developed as a potential non-invasive ablation method for multiple applications including the treatment of benign prostatic hyperplasia (Hempel et al 2011;Roberts et al 2014;Schuster et al 2018), thrombus obstruction (Maxwell et al 2011a;Gerhardson et al 2017;Zhang et al 2017), and cancer (Styn et al 2010;Vlaisavljevich et al 2013b;Smolock et al 2018;Worlikar et al 2018;Longo et al 2019;Qu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Gerhardson et al showed that histotripsy can liquefy a large clot volume through an intact human skull as fast as 16 ml/min without overheating the skull [ 130 ]. Gerhardson et al [ 137 ] also designed and built a catheter-based hydrophone, which allows for intra-procedural aberration correction. This catheter-based hydrophone combined with a neuronavigation system would allow the histotripsy ICH treatment to be performed without requiring an MRI scanner which makes it more suitable for an emergent procedure.…”
Section: Pre-clinical Applicationsmentioning
confidence: 99%
“…In addition, the feasibility of histotripsy in the treatment of intracerebral hemorrhage (ICH) has also been demonstrated by some studies. Patients with ICH can be treated by histotripsy to liquefy the blood clot in the brain and then by catheterization to withdraw the liquefied volume ( 85 ). Gerhardson et al ( 86 ) showed that using histotripsy with EFS to correct the aberration can liquefy massive clots through the human skull at a rate of 16 mL/min without overheating the skull.…”
Section: Application Of Histotripsy In Animal Modelsmentioning
confidence: 99%